2013
DOI: 10.12777/ijse.5.1.31-34
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Ni3(Si,Ti) in Hydrochloric Acid Solution

Abstract: -The corrosion behaviour of the intermetallic compounds Ni3(Si,Ti)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…On the other hand, the compounds have shown to be suceptible to enviromental embrittlement (specifically hydrogen embrittlement) at ambient temperature in moisture in air and hydrogen gas (Kaneno et al,2011 ;Takasugi et al, 1993a ;Takasugi et al, 1993b). The addition of boron of Ni3(Si,Ti) was to suppres enviromental embrittlement (Takasugi et al, 1995), although the intergranular attack were observed for this as-homogenized Ni3(Si,Ti) compound (Priyotomo et al,2011) and Ni3(Si,Ti) compound after thermomechanical process (Priyotomo et al,2013) in acidic solutions, which took place by boron segregation at grain boundaries.…”
mentioning
confidence: 97%
“…On the other hand, the compounds have shown to be suceptible to enviromental embrittlement (specifically hydrogen embrittlement) at ambient temperature in moisture in air and hydrogen gas (Kaneno et al,2011 ;Takasugi et al, 1993a ;Takasugi et al, 1993b). The addition of boron of Ni3(Si,Ti) was to suppres enviromental embrittlement (Takasugi et al, 1995), although the intergranular attack were observed for this as-homogenized Ni3(Si,Ti) compound (Priyotomo et al,2011) and Ni3(Si,Ti) compound after thermomechanical process (Priyotomo et al,2013) in acidic solutions, which took place by boron segregation at grain boundaries.…”
mentioning
confidence: 97%
“…Fig 1. The microstructure of Ni3(Si,Ti)+2Mo with dual phases ( L12 and mixture region) that were observed, had small and equiaxial grains in L12 phase. Furthermore, Kaneno and co-workers have already investigated the microstructure of this compound in detail [5]. Fig.…”
Section: Corrosion Test 1)mentioning
confidence: 99%